Parathyroid carcinoma: review of a problematic case (Medical Journal of Indonesia, 2012)
Parathyroid carcinoma (PTCA) is a rare neoplasm that accounts for less than 1% of primary hyperparathyroidism cases. Several clinical and biochemical features can directing to PTCA, but accurate pre and intraoperative diagnosis are still difficult. This study presents a case of PTCA that diagnosed postoperatively with a discussion of microscopic feature. The surgical exploration revealed an enlarged parathyroid mass which invade recurrent laryngeal nerve and right thyroid gland. Histologic features showed tumor nodules separated by thick fibrous band with capsular invasion and local infiltration to adjacent tissues. The final diagnosis of PTCA was made based on clinical feature and specimens examination. (Med J Indones. 2012;21:170-4)